AUDIT MARKET SHARE AND AUDITORS' INDUSTRY SPECIALISATION: EFFECTS OF DIFFERENT BASES OF MEASUREMENT - Takiah Mohd. Iskandar,; Aini Aman , (Asian Academy of Management Journal, 2003)
Past studies have examined audit market concentration and auditors' industry specialisation within different countries including the US (Zeff & Fossum, 1967; Rhode, Whitsell & Kelsey, 1974; Schiff & Fried, 1976; Eichenseher & Danos, 1981; Danos & Eichenseher, 1982), Australia (Craswell & Taylor, 1991; Craswell, Francis & Taylor, 1994), and Malaysia (Iskandar, Maelah & Aman, 2000). These studies have employed different bases to measure audit market concentration and auditors' industry specialisation. It is argued that, due to the different bases used to measure audit market share, results of the studies may not be comparable. The differences in research findings may be driven by the differences in the bases of measurement. Hence, the results do not reflect the actual market distribution and industry expertise of the auditor. The objective of this study is to provide evidence to support the argument that differences in research results are due to differences in the methods used to measure audit market concentration and auditors' industry specialisation. Results show that, based on Malaysian empirical data, audit market share and industry specialisation vary significantly with different bases of measurement employed.